Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Ab initio study of strain effects on the quasiparticle bands and effective masses in silicon - Bouhassoune, Mohammed; Schindlmayr, Arno (Advances in Condensed Matter Physics)
Using ab initio computational methods, we study the structural and electronic properties of strained silicon, which has emerged as a promising technology to improve the performance of silicon-based metal-oxide-semiconductor field-effect transistors. In particular, higher electron mobilities are observed in n-doped samples with monoclinic strain along the [110] direction, and experimental evidence relates this to changes in the effective mass as well as the scattering rates. To assess the relative importance of these two factors, we combine density-functional theory in the local-density approximation with the GW approximation for the electronic self-energy and investigate the effect of uniaxial and biaxial strains along the [110] direction on the structural and electronic properties of Si. Longitudinal and transverse components of the electron effective mass as a function of the strain are derived from fits to the quasiparticle band structure and a diagonalization of the full effective-mass tensor. The changes in the effective masses and the energy splitting of the conduction-band valleys for uniaxial and biaxial strains as well as their impact on the electron mobility are analyzed. The self-energy corrections within GW lead to band gaps in excellent agreement with experimental measurements and slightly larger effective masses than in the local-density approximation.

Projective filtering of the fundamental eigenmode from spatially multimode radiation - Pérez, A. M.; Sharapova, Polina; Straupe, S. S.; Miatto, F. M.; Tikhonova, O. V.; Leuchs, G.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Direct Schmidt number measurement of high-gain parametric down conversion - Dyakonov, I V; Sharapova, Polina; Iskhakov, T Sh; Leuchs, G (Laser Physics Letters)
Keywords: Physics and Astronomy (miscellaneous); Instrumentation

Schmidt modes in the angular spectrum of bright squeezed vacuum - Sharapova, Polina; Pérez, A. M.; Tikhonova, O. V.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Giant narrowband twin-beam generation along the pump-energy propagation direction - Pérez, Angela M.; Spasibko, Kirill Yu; Sharapova, Polina; Tikhonova, Olga V.; Leuchs, Gerd; Chekhova, Maria V. (Nature Communications)
Abstract Walk-off effects, originating from the difference between the group and phase velocities, limit the efficiency of nonlinear optical interactions. While transverse walk-off can be eliminated by proper medium engineering, longitudinal walk-off is harder to avoid. In particular, ultrafast twin-beam generation via pulsed parametric down-conversion and four-wave mixing is only possible in short crystals or fibres. Here we show that in high-gain parametric down-conversion, one can overcome the destructive role of both effects and even turn them into useful tools for shaping the emission. In our experiment, one of the twin beams is emitted along the pump Poynting vector or its group velocity matches that of the pump. The result is markedly enhanced generation of both twin beams, with the simultaneous narrowing of angular and frequency spectrum. The effect will enable efficient generation of ultrafast twin photons and beams in cavities, waveguides and whispering-gallery mode resonators.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)
We present radiation mechanism exhibited by a higher order soliton. In a course of its evolution the higher-order soliton emits polychromatic radiation resulting in formation of multipeak frequency comb-like spectral band. The shape and spectral position of this band can be effectively controlled by the relative strength of the third order dispersion. An analytical description is corroborated by numerical simulations. It is shown that for longer pulses the described effect persists also under the action of higher order perturbations such as Raman and self-steepening.

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Yulin, A. V.; Driben, R. (Optics Letters)
The effect of mutual interactions between dark solitons and dispersive waves is investigated numerically and analytically. The condition of the resonant scattering of dispersive waves on dark solitons is derived and compared against the results of the numerical simulations. It is shown that the interaction with intense dispersive waves affects the dynamics of the solitons by accelerating, decelerating, or destroying them. It is also demonstrated that two dark solitons can form a cavity for dispersive waves bouncing between the two dark solitons. The differences of the resonant scattering of the dispersive waves on dark and bright solitons are discussed. In particular, we demonstrate that two dark solitons and a dispersive wave bouncing in between them create a solitonic cavity with convex “mirrors,” unlike the concave “mirror” in the case of bright solitons.

Defacto-a multilingual fact validation interface - Speck, René; Esteves, Diego; Lehmann, Jens; Ngomo, A-C Ngonga (14th International Semantic Web Conference (ISWC 2015), 11-15 October 2015, Bethlehem, Pennsylvania, USA (Semantic Web Challenge Proceedings))

Semantic clustering of website based on its hypertext structure - Salin, Vladimir; Slastihina, Maria; Ermilov, Ivan; Speck, René; Auer, Sören; Papshev, Sergey (Knowledge Engineering and Semantic Web: 6th International Conference, KESW 2015, Moscow, Russia, September 30-October 2, 2015, Proceedings 6)

L’élaboration d’une grammaire pédagogique à partir de corpus : l’exemple du subjonctif - Bürgel, Christoph; Siepmann, Dirk (Grammatikographie und Didaktische Grammatik – gestern, heute, morgen. Gedenksymposium für Hartmut Kleineidam (†). Saarbrücker Schriften zur Linguistik und Fremdsprachendidaktik (SSLF))

Seelenheil und Prestige. Die Erzbruderschaft der Gonfalone als Loskauforganisation für den Kirchenstaat - Priesching, Nicole (Gefangenenloskauf im Mittelmeerraum. Ein interreligiöser Vergleich)

Einleitung - Priesching, Nicole; Grieser, Heike (Gefangenenloskauf im Mittelmeerraum. Ein interreligiöser Vergleich)

Defacto—temporal and multilingual deep fact validation - Gerber, Daniel; Esteves, Diego; Lehmann, Jens; Bühmann, Lorenz; Usbeck, Ricardo; Ngomo, Axel-Cyrille Ngonga; Speck, René (Journal of Web Semantics)

GERBIL: general entity annotator benchmarking framework - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Baron, Ciro; Both, Andreas; Brümmer, Martin; Ceccarelli, Diego; Cornolti, Marco; Cherix, Didier; Eickmann, Bernd (Proceedings of the 24th international conference on World Wide Web)

CETUS–a baseline approach to type extraction - Röder, Michael; Usbeck, Ricardo; Speck, René; Ngomo, Axel-Cyrille Ngonga (Semantic Web Evaluation Challenges: Second SemWebEval Challenge at ESWC 2015, Portorož, Slovenia, May 31-June 4, 2015, Revised Selected Papers)